Agonista versus antagonista do GnRH em ciclos de reprodução assistida: DNA fragmentação e apoptose das células da granulosa - Lavorato, Heloisa Lopes [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
Os agonistas do hormônio liberador de gonadotrofina (Gonadotropin-releasing hormone / GnRH) foram introduzidos na estimulação ovariana para fertilização in-vitro (FIV) com o objetivo de evitar o pico prematuro do hormônio luteinizante (LH). Embora sejam acompanhados de algumas desvantagens, os agonistas do GnRH tornaram-se bem aceitos na prática clínica com sua utilização sendo associada a aumento das taxas de gravidez. O desenvolvimento dos antagonistas do GnRH, capazes de bloqueio imediato da hipófise ofereceu uma nova opção terapêutica. Estudos comparativos entre os dois análogos têm sugerido que o uso de antagonistas está associado a uma menor duração do estímulo ovulatório e uma diminuição da incidência de síndrome de hiperestimulação ovariana, enquanto as taxas de gravidez e de nascidos vivos não parecem sofrer influências significativas do tipo de análogo do GnRH utilizado. Por outro lado, os agonistas do GnRH apresentam outras aplicações em ciclos de reprodução assistida além do bloqueio hipofisário

The expression of the gonadotrophin-releasing hormone (GnRH) receptor has been demonstrated in the human ovary, and it has therefore been suggested that GnRH agonists have different effects on the intraovarian system compared with GnRH antagonists, particularly in the granulosa cell (GC) layer. This study aimed to compare the level of apoptosis and DNA fragmentation in human GCs exposed to agonist or antagonist of GnRH in intracytoplasmic sperm injection (ICSI) cycles supplemented with recombinant LH (r-LH). Patients without ovulatory dysfunction aged ≤ 37 years and in the first ICSI cycle were prospectively randomised to receive either a long GnRH agonist protocol or a multi-dose antagonist protocol. In both groups, the GCs were collected during oocyte denudation and separated from blood cells by centrifugation on a 60% isolate solution. It should be emphasized that the study examined only GCs that had been directly detached from the oocyte cumulus complexes. The GCs were then analyzed for DNA fragmentation by TUNEL assay and for apoptosis using annexin-V. The primary outcome measurements were given as the percentage of GCs with DNA fragmentation and apoptosis out of the total number of GCs analyzed. The comparison of the agonist versus the antagonist group was performed using the Mann-Whitney test
Keywords: Apoptose; Reprodução humana; Fecundidade humana